2011
DOI: 10.1042/cbi20100899
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and characteristics of the enhanced green fluorescent protein gene transgenic goat neural stem cells cultured in attached and non‐attached plates

Abstract: The aims of this study were (i) to determine whether NSCs (neural stem cells) could be isolated from the brain of embryonic day 98 fetal goat, (ii) to determine if these stem cells have the capability of multipotent differentiation following transfection with a reporter gene, EGFP (enhanced green fluorescent protein) and (iii) to study the characteristics of the stem cells cultured in attached and non‐attached plates. NSCs were isolated from embryonic day 98 fetal goat brain, transfected with EGFP gene using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…These NSCs have the capacity of self-renewal and differentiation (Zheng et al, 2010). Zheng et al (2011) succeeded in isolating stem cells from embryonic (day 98) foetal goat brain and transfecting EGFP gene into the cells. In vitro, piglet NSPs proliferated as neurospheres, expressed typical protein of neural progenitors, nestin, and a range of well-established neurodevelopmental markers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These NSCs have the capacity of self-renewal and differentiation (Zheng et al, 2010). Zheng et al (2011) succeeded in isolating stem cells from embryonic (day 98) foetal goat brain and transfecting EGFP gene into the cells. In vitro, piglet NSPs proliferated as neurospheres, expressed typical protein of neural progenitors, nestin, and a range of well-established neurodevelopmental markers.…”
Section: Introductionmentioning
confidence: 99%
“…Ara et al (2010) reported the characterisation of neural stem/progenitor cells (NSP) population from subventricular zone (SVZ) of neonatal piglet brain using in vivo and in vitro systems, and showed that the nestin and vimentin-positive neural progenitor cells are present in the SVZ of the lateral ventricles of neonatal piglet brain. Zheng et al (2011) showed that late stage foetus could be used for isolation of NSCs, which were characterised properly along with differentiation into cells of neural lineages. Zhao et al (2012) derived NSCs from enhanced green fluorescent protein (EGFP) transgenic porcine foetuses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among domestic animals, isolation, propagation of these cells and their in vitro differentiation to neural cells were carried out by Zheng et al (2011) and Zhao et al . (2012) in porcine.…”
Section: Introductionmentioning
confidence: 99%